Various CVD-grown ZnO nanostructures for nanodevices and interdisciplinary applications - The-Long Phan; Le Viet Cuong; Vu Dinh Lam; Ngoc Toan Dang (Beilstein Journal of Nanotechnology)
This work presents a simple chemical vapour deposition (CVD) method to grow ZnO nanostructures. By annealing Zn powder under atmospheric pressure conditions, we collected nanocrystals with various morphologies, including rods, pencils, sheets, combs, tetrapods, and multilegs. Raman scattering study reveals that the samples are monophasic with a hexagonal structure, and fall into the P63mc space group. Depending on the morphology and crystal quality, their photoluminescence spectra have only a strong UV emission associated with the exciton radiative recombination, or both UV and defect-related visible emissions with their relative intensity ratio varying with the excitation power density. The obtained results prove that ZnO exhibits many novel nanostructures that can foster the development of next-generation optoelectronic nanodevices and new applications in biological and biomedical fields.